Expression of transcription factors involved in epithelial-to-mesenchymal transition of the breast cancer cell line MCF-7 co-cultured with adipose tissue mesenchymal stem cells - Tien, Vu Thi; Hoang Duc, Le; Van Ngoc, Bui; Trung Nam, Nguyen (Vietnam Journal of Biotechnology, 2023)
Breast cancer is the most frequently diagnosed cancer in women globally. The tumor microenvironment plays a vital role in epithelial-to-mesenchymal transition (EMT), leading to the invasion and metastasis of cancer cells. The tumor microenvironment includes all components of the tumor cells, including the extracellular matrix, tumor vasculature, mesenchymal stem cells, immune cells, and fibroblasts. Understanding the interactions between mesenchymal stem cells and cancer cells is essential in determining the role of mesenchymal stem cells in diagnosing and treating breast cancer. In this study, we present the result of co-culture between adipose tissue mesenchymal stem cells (ADMSCs) and breast cancer cells (MCF-7 cell line) and determine the expression levels of transcription factors involved in EMT, including Twist and Snail. The results showed that the proliferation of MCF-7 co-cultured with ADMSCs was not increased compared to MCF-7 mono-cultured. Determination of gene expression levels by qRT-PCR revealed a significant increase in the EMT-related transcription factors (Twist and Snail) in breast cancer cells upon co-culture with ADMSCs. There were also significant differences between the expression levels of IL-6 and AhR in MCF-7 cells co-cultured with ADMSCs and MCF-7 cells mono-cultured. The results suggested that ADMSCs promoted the EMT of MCF-7 cells, potentially via AhR/NF-κB pathways.